METHOD OF EVALUATION THE EFFICIENCY OF FUNCTIONING OF THE TELECOMMUNICATION SYSTEMS OF SPECIAL PURPOSE - Катеринчук, І. С.; Рачок, Р. В.; Мул, Д. А.; Басараб, О. К. (Science-based technologies, 2014)
Quality of solving different tasks of human activities, including law enforcement activity depends on functioning of telecommunication systems. Telecommunication systems expertise research doesn’t reveal the conditions of the special purpose telecommunication systems functioning, therefore it is important to improve the methods of evaluation the efficiency of special-purpose telecommunication systems considering fuzziness of individual parameters and characteristics of construction. The article analyzed and selected indicators important for assessing the efficiency of special-purpose telecommunication systems. The research developed the scheme of forming up the complex efficiency index of special-purpose telecommunication system and worked out the analytical expression of this index. On the basis of the scheme and the expression the method of evaluation the efficiency of special-purpose telecommunication system generated. This method make possible to evaluate the effectiveness and synthesis the special-purpose telecommunication system of certain requirements.